A novel diffuse large B-cell lymphoma-associated cancer testis antigen encoding a PAS domain protein. - Liggins, A; Brown, P; Asker, K; Pulford, K; Banham, A (2004)
Here we report that the OX-TES-1 SEREX antigen, which showed immunological reactivity with serum from four out of 10 diffuse large B-cell lymphoma (DLBCL) patients, is encoded by a novel gene, PAS domain containing 1 (PASD1). PASD1_v1 cDNA encodes a 639 amino-acid (aa) protein product, while an alternatively spliced variant (PASD1_v2), lacking intron 14, encodes a 773 aa protein, the first 638 aa of which are common to both proteins. The PASD1-predicted protein contains a PAS domain that, together with a putative leucine zipper and nuclear localisation signal, suggests it encodes a transcription factor. The expression of PASD1_v1 mRNA was confirmed by RT-PCR in seven DLBCL-derived cell lines, while PASD1_v2 mRNA appears to be preferentially expressed in cell lines derived from non-germinal centre DLBCL. Immunophenotyping studies of de novo DLBCL patients' tumours with antibodies to CD10, BCL-6 and MUM1 indicated that two patients mounting an immune response to PASD1 were of a poor prognosis non-germinal centre subtype. Expression of PASD1 mRNA was restricted to normal testis, while frequent expression was observed in solid tumours (25 out of 68), thus fulfilling the criteria for a novel cancer testis antigen. PASD1 has potential for lymphoma vaccine development that may also be widely applicable to other tumour types.